Bankruptcy of Foreign Enterprises in the PRC: An Interpretation of the Rules Concerning Bankruptcy of Foreign Related Companies in the Shenzhen Special Economic Zone - Toronto, Steven L. (Columbia Journal of Asian Law, 1990)
Throughout the 1980s foreign investment in the People’s Republic of China (PRC) grew rapidly. The PRC’s vast domestic markets coupled with the availability of low cost labor provided incentives that foreign investors found difficult to resist. By the end of the decade, however, the initial enthusiasm of foreign investors gave way to a more realistic view of the practical difficulties of investing in the PRC. The events culminating in the Tian’anmen Square tragedy and the subsequent political crackdown caused further erosion in foreign investors’ confidence and deterioration of the PRC’s investment cli- mate. Changes in the investment climate have been reflected in the performance of foreign investments in the PRC, many of which now face poor profit outlooks, chronic operating losses and no real hope of financial success. As the investment climate has deteriorated an increasing number of foreign investors and creditors of foreign ventures in the PRC have been faced with the specters of business failure and bankruptcy.